MULTIPLE CHOICE QUESTIONS
Question 1:
Which of the following expressions is a polynomial in one variable?
(a)
(b)
(c)
(d) x10 + y5 + 8
Answer 1:
(c)
Clearly, is a polynomial in one variable because it has only non-negative integral powers of x.
Question 2:
Which of the following expression is a polynomial?
(a)
(b)
(c)
(d)
Answer 2:
(d)
We have:
It a polynomial because it has only non-negative integral powers of x.
Question 3:
(a)
(b)
(c) y
(d)
Answer 3:
(c) y
y is a polynomial because it has a non-negative integral power 1.
Question 4:
Which of the following is a polynimial?
(a)
(b)
(c)
(d) −4
Answer 4:
(d) −4
4 is a constant polynomial of degree zero.
Question 5:
Which of the following is a polynomial?
(a) x−2 + x−1 + 3
(b) x + x−1 + 2
(c) x−1
(d) 0
Answer 5:
(d) 0
0 is a polynomial whose degree is not defined.
Question 6:
Which of the following is quadratic polynomial?
(a) x + 4
(b) x3 + x
(c) x3 + 2x + 6
(d) x2 + 5x + 4
Answer 6:
(d) x2 + 5x + 4
is a polynomial of degree 2. So, it is a quadratic polynomial.
Question 7:
Which of the following is a linear polynomial?
(a) x + x2
(b) x + 1
(c) 5x2 − x + 3
(d)
Answer 7:
(b) x + 1
Clearly, is a polynomial of degree 1. So, it is a linear polynomial.
Question 8:
Which of the following is a binomial?
(a) x2 + x + 3
(b) x2 + 4
(c) 2x2
(d)
Answer 8:
(b) x2 + 4
Clearly, is an expression having two non-zero terms. So, it is a binomial.
Question 9:
is a polynomial of degree
(a)
(b) 2
(c) 1
(d) 0
Answer 9:
(d) 0
is a constant term, so it is a polynomial of degree 0.
Question 10:
Degree of the zero polynomial is
(a) 1
(b) 0
(c) not defined
(d) none of these
Answer 10:
(c) not defined
Degree of the zero polynomial is not defined.
Question 11:
Zero of the zero polynomial is
(a) 0
(b) 1
(c) every real number
(d) not defined
Answer 11:
(d) not defined
Zero of the zero polynomial is not defined.
Question 12:
If p(x) = x = 4, then p(x) + p(−x) = ?
(a) 0
(b) 4
(c) 2x
(d) 8
Answer 12:
(d) 8
Let:
Thus, we have:
= 4 + 4
=8
Question 13:
If , then ?
(a) 0
(b) 1
(c)
(d) −1
Answer 13:
(b) 1
= 8 8 + 1
= 1
Question 14:
If p(x) = 5x – 4x2 + 3 then p(–1) =?
(a) 2
(b) –2
(c) 6
(d) –6
Answer 14:
p(x) = 5x – 4x2 + 3
Putting x = –1 in p(x), we get
p(–1) = 5 × (–1) – 4 × (–1)2 + 3 = –5 – 4 + 3 = –6
Hence, the correct answer is option (d).
Question 15:
If (x51 + 51) is divided by (x + 1) then the remainder is
(a) 0
(b) 1
(c) 49
(d) 50
Answer 15:
Let f(x) = x51 + 51
By remainder theorem, when f(x) is divided by (x + 1), then the remainder = f(−1).
Putting x = −1 in f(x), we get
f(−1) = (−1)51 + 51 = −1 + 51 = 50
∴ Remainder = 50
Thus, the remainder when (x51 + 51) is divided by (x + 1) is 50.
Hence, the correct answer is option (d).
Question 16:
If (x + 1) is a factor of (2x2 + kx), then k = ?
(a) 4
(b) −3
(c) 2
(d) –2
Answer 16:
(c) 2
Question 17:
When p(x) = x4 + 2x3 − 3x2 + x − 1 is divided by (x − 2), the remainder is
(a) 0
(b) −1
(c) −15
(d) 21
Answer 17:
(d) 21
By the remainder theorem, we know that when p(x) is divided by (x 2), the remainder is p(2).
Thus, we have:
Question 18:
When p(x) = x3 − 3x2 + 4x + 32 is divided by (x + 2), the remainder is
(a) 0
(b) 32
(c) 36
(d) 4
Answer 18:
(d) 4
By the remainder theorem, we know that when p(x) is divided by (x + 2), the remainder is p(2).
Now, we have:
Question 19:
When p(x) = 4x3 − 12x2 + 11x − 5 is divided by (2x − 1), the remainder is
(a) 0
(b) −5
(c) −2
(d) 2
Answer 19:
(c) −2
By the remainder theorem, we know that when p(x) is divided by (2x 1), the remainder is .
Now, we have:
Question 20:
When p(x) = x3 – ax2 + x is divided by (x – a), the remainder is
(a) 0
(b) a
(c) 2a
(d) 3a
Answer 20:
By remainder theorem, when p(x) = x3 – ax2 + x is divided by (x – a), then the remainder = p(a).
Putting x = a in p(x), we get
p(a) = a3 – a × a2 + a = a3 – a3 + a = a
∴ Remainder = a
Hence, the correct answer is option (b).
Question 21:
When p(x) = x3 + ax2 + 2x + a is divided by (x + a), the remainder is
(a) 0
(b) −1
(c) −15
(d) 21
Answer 21:
(c) −a
By the remainder theorem, we know that when p (x) is divided by (x + a), the remainder is p (−a).
Thus, we have:
Question 22:
(x + 1) is a factor of the polynomial
(a) x3 + x2 – x + 1
(b) x3 + 2x2 – x – 2
(c) x3 + 2x2 − x + 2
(d) x4 + x3 + x2 + 1
Answer 22:
(b) x3 − 2x2 − x − 2
Let:
f(x) = x3 − 2x2 − x − 2
By the factor theorem, (x + 1) will be a factor of f(x) if f (1) = 0.
We have:
Hence, (x + 1) is a factor of .
Question 23:
Zero of the polynomial p(x) = 2x + 5 is
(a)
(b)
(c)
(d)
Answer 23:
The zero of the polynomial p(x) can be obtained by putting p(x) = 0.
Hence, the correct answer is option (b).
Question 24:
The zeros of the polynomial p(x) = x2 + x – 6 are
(a) 2, 3
(b) –2, 3
(c) 2, –3
(d) –2, –3
Answer 24:
The given polynomial is p(x) = x2 + x – 6.
Putting x = 2 in p(x), we get
p(2) = 22 + 2 – 6 = 4 + 2 – 6 = 0
Therefore, x = 2 is a zero of the polynomial p(x).
Putting x = –3 in p(x), we get
p(–3) = (–3)2 – 3 – 6 = 9 – 9 = 0
Therefore, x = –3 is a zero of the polynomial p(x).
Thus, 2 and –3 are the zeroes of the given polynomial p(x).
Hence, the correct answer is option (c).
Question 25:
The zeros of the polynomial p(x) = 2x2 + 5x – 3 are
(a)
(b)
(c)
(d)
Answer 25:
The given polynomial is p(x) = 2x2 + 5x – 3.
Putting in p(x), we get
Therefore, is a zero of the polynomial p(x).
Putting x = –3 in p(x), we get
Therefore, x = –3 is a zero of the polynomial p(x).
Thus, and –3 are the zeroes of the given polynomial p(x).
Hence, the correct answer is option (b).
Question 26:
The zeros of the polynomial p(x) = 2x2 + 7x – 4 are
(a)
(b)
(c)
(d)
Answer 26:
The given polynomial is p(x) = 2x2 + 7x – 4.
Putting in p(x), we get
Therefore, is a zero of the polynomial p(x).
Putting x = –4 in p(x), we get
Therefore, x = –4 is a zero of the polynomial p(x).
Thus, and –4 are the zeroes of the given polynomial p(x).
Hence, the correct answer is option (c).
Question 27:
If (x + 5) is a factor of p(x) = x3 − 20x + 5k, then k = ?
(a) −5
(b) 5
(c) 3
(d) −3
Answer 27:
(b) 5
Question 28:
If (x + 2) and (x − 1) are factors of (x3 + 10x2 + mx + n), then
(a) m = 5, n = −3
(b) m = 7, n = −18
(c) m = 17, n = −8
(d) m = 23, n = −19
Answer 28:
(b) m = 7, n = −18
Let:
Now,
(x + 2) is a factor of p(x).
So, we have p(2)=0
Now,
Also,
(x 1) is a factor of p(x).
We have:
p(1) = 0
By substituting the value of m in (i), we get n = −18.
∴ m = 7 and n = −18
Question 29:
If (x100 + 2x99 + k) is divisible by (x + 1), then the value of k is
(a) 1
(b) 2
(c) −2
(d) −3
Answer 29:
(a) 1
Let:
Now,
Question 30:
For what value of k is the polynomial p(x) = 2x3 − kx + 3x + 10 exactly divisible by (x + 2)?
(a)
(b)
(c) 3
(d) −3
Answer 30:
(d) −3
Let:
Now,
Question 31:
The zeroes of the polynomial p(x) = x2 − 3x are
(a) 0, 0
(b) 0, 3
(c) 0, −3
(d) 3, −3
Answer 31:
(b) 0, 3
Let:
Now, we have:
Question 32:
The zeroes of the polynomial p(x) = 3x2 − 1 are
(a) and 3
(b)
(c)
(d)
Answer 32:
(d)
Let:
Hence, the correct answer is option D.
No comments:
Post a Comment